We must never forget: remembering the 1931 Estevan strike - Anderson, Don (Briarpatch, 1997)
There was an electric feeling in the air as hundreds of people gathered to honour the strikers and pay tribute to the three miners killed in [Estevan] on Black Tuesday. A Highland Pipe band played while the crowd visited, ate hot dogs and were entertained by a Miners' Choir formed especially for the occasion. The crowd was receptive to all speakers, but saved its loudest applause for [Pete Gemby].
Keywords: Coal mines; Coal mining; History; Memorials & monuments; Political Science